2020
DOI: 10.1097/j.pain.0000000000002014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Notch signaling pathway in the anterior cingulate cortex is involved in the pathological process of neuropathic pain

Abstract: This study reveals interfering Notch signaling pathway of anterior cingulate cortex in early phase prevents neuropathic pain progress by inhibiting the potentiation of synaptic transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Later, the injection of propofol downregulated the expression of North family proteins. Consistently, another research reported that the activation of the Notch or Hes1 signaling plays a role in NP by strengthening excitatory synaptic transmission (Duan 2021). The Notch signaling in uences the choice between the excitatory or inhibitory cell fatesin the developing spinal cord to ensure the proper generation of excitatory neurons from the sensory interneuron progenitors (Xie 2015a).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Later, the injection of propofol downregulated the expression of North family proteins. Consistently, another research reported that the activation of the Notch or Hes1 signaling plays a role in NP by strengthening excitatory synaptic transmission (Duan 2021). The Notch signaling in uences the choice between the excitatory or inhibitory cell fatesin the developing spinal cord to ensure the proper generation of excitatory neurons from the sensory interneuron progenitors (Xie 2015a).…”
Section: Discussionmentioning
confidence: 52%
“…Notch signaling is reported to possess importance in many biological processes, including cell proliferation, cell death and differentiation (Arumugam et al 2018). Previous research has con rmed that the expression of Notch signaling is augmented and activated after NP (Duan et al 2021). From all above information, we hypothesized that propofol could regulate the expression of miR-140-3p and JAG1 to play a role in alleviating NP, and the paper aims to gure out the underlying mechanism of propofol to relieve NP and seek a novel therapeutic target of NP.…”
Section: Introductionmentioning
confidence: 95%
“…Expectedly, intervention with propofol brought about down-regulation of North family protein expressions. Consistently, another research reported that activation of the Notch or HES1 signaling plays a role in NP by strengthening excitatory synaptic transmission (Duan, Shen, 2021). In addition, Notch signaling influences the choice between the excitatory or inhibitory cell fates in the developing spinal cord to ensure the proper generation of excitatory neurons from the sensory interneuron progenitors (Xie, Jia, 2015a).…”
Section: Discussionmentioning
confidence: 80%
“…Notch signaling is reported to possess importance in numerous biological processes, including cell proliferation, cell death, and differentiation (Arumugam et al, 2018). Previous studies have further confirmed that Notch signaling expressions are elevated and activated after the advent of NP (Duan et al, 2021). In lieu of all these findings and data, we hypothesized that propofol could regulate the expression of miR-140-3p and JAG1 to play a role in alleviating NP and performed a series of experiments to elucidate the underlying mechanism of propofol to relieve NP and seek a novel therapeutic target of NP.…”
Section: Introductionmentioning
confidence: 90%
“…( Geppetti et al, 2015 , Nourbakhsh et al, 2018 ) There is evidence from prior studies that some of the identified pathways are involved in chronic pain conditions and pain management. ( Chidambaran et al, 2019 , Pedersen et al, 2015 , Duan et al, 2021 , Wang and Burrell, 2018 , Hossain et al, 2020 , Siuda et al, 2015 , Isensee et al, 2017 , Gomes et al, 2020 , Louwies et al, 2019 , Montesino-Goicolea et al, 2020 ) For instance, Montesino-Goicolea et al reported that enrichment of GABA Receptor Signaling pathways by differentially methylated genes between adults chronic pain and healthy controls. ( Montesino-Goicolea et al, 2020 ) Also, enrichment of GABA Receptor Signaling pathways have previously been associated with chronic postoperative pain, ( Chidambaran et al, 2019 ) while Opioid Signaling and Endocannabinoid Neuronal Synapse Pathways have previously been associated with addiction and pain management.…”
Section: Discussionmentioning
confidence: 99%